Diction Model and Language Format of Notarial Contracts in Indonesia - Anita Puspawati (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
The language used in contracts must adhere to the rules of the Indonesian language without diminishing the legal purpose and function, while also serving as a foundation for legal reform in Indonesia. This research is qualitative in nature, aiming to compare legal language in contracts with the standard Indonesian language. The data collected in this study consists of secondary data supported by field research data (primary data). Data collection techniques were carried out through document/literature review, supplemented by observational participation and in-depth interviews. This research identifies the influence of foreign languages, particularly Dutch, which still affects the structure of contract language today. Contract language, which should follow standard Indonesian language rules, often uses unclear, ambiguous, and inefficient terms, which can confuse readers, especially the general public. The results show that the language structure of notarial contracts remains rigid and often improperly structured, leading to potential misinterpretations. However, by using simpler language that adheres to Indonesian language rules, it is hoped that these contracts can be more widely understood by the public, reducing misinterpretations and enhancing clarity and efficiency in legal practice.